Psychedelic treatment of functional neurological disorder: a systematic review. (May 2020) - Butler, Matthew; Seynaeve, Mathieu; Nicholson, Timothy R.; Pick, Susannah; Kanaan, Richard A.; Lees, Andrew; Young, Allan H.; Rucker, James
Functional neurological disorder (FND), formerly known as conversion disorder, causes a high burden of disability and distress, and is amongst the most commonly encountered conditions in neurology clinics and neuropsychiatric services, yet the therapeutic evidence base is somewhat limited. There has been recent interest in the therapeutic potential of psychedelics such as psilocybin and lysergic acid diethylamide (LSD), and in recent studies psychedelics have shown promise in treating a range of neuropsychiatric conditions. Modification of neural circuits associated with self-representation is thought to underlie some of this effect, and as some contemporary theories of FND focus on aberrant somatic self-representation, psychedelics may therefore represent an unexplored treatment option for FND. We systematically reviewed studies involving the use of psychedelics in FND. Nine studies published between 1954 and 1967, with a total of 26 patients, were identified. Due to restriction of licencing of psychedelic drugs since this period, no modern studies were identified. In most cases, patients received a course of psychotherapy with variable adjunctive administration of psychedelics (in a combination known as 'psycholytic therapy'), with protocols varying between studies. Of those treated, 69% ( n  = 18) were found to have made at least some recovery on heterogeneous and subjective clinician-rated criteria. Adverse events were mostly mild and transient; however, at least one patient terminated the study due to distressing effects. All included studies were of low quality, often lacking control groups and valid outcome measures. Although no conclusions on efficacy may be drawn from these data, further research may help to determine whether psychedelics offer a feasible, safe and effective treatment for FND.